Efficacy and Safety of Pulsed Radiofrequency of Dorsal Root Ganglion in Elderly Patient Population With Acute and Subacute Zoster-Related Pain - Gözde Dağıstan; Serdar Erdine (Pain Research and Management)
Conclusions: Interventional pain treatment should be applied as soon as possible in the elderly patient group who do not respond to first-line medical treatment or cannot tolerate medical treatment due to its side effects and who have a high risk of developing PHN compared to other age groups. DRG PRF, applied in the early period of medical treatment-resistant acute HZ, is safe and effective, preventing the progression to PHN.